The concept of transcendence in philosophy and theology - Petrov, George Daniel (Technium Social Sciences Journal, 2021)
The transcendence of God is the most sensitive and profound subject that could be addressed by the most enlightened minds of the world. In sketching this concept, the world of philosophy and that of theology are trying the impossible: to define the Absolute. Each approach is different, the first being subjected to reason, reaching specific conclusions, and the second, by understanding God's Personal character, appealing to the experience of living your life in God. The debate between the two worlds, that of philosophy and that of theology can only bring a plus to knowledge, while impressing any wisdom lover.